Dramatic Response of Leptomeningeal Carcinomatosis to Nivolumab in PD-L1 Highly Expressive Non-small Cell Lung Cancer: A Case Report - Arias Ron, David; Labandeira, Carmen M.; Areses Manrique, María Carmen; Sampedro Domarco, Paula; Abdulkader, Ihab; García-Mata, Jesús; Rolfo, Christian; González-Rivas, Diego; Fírvida, Jose Luis (Frontiers in Oncology, 2019)
In a patient who had been diagnosed of located squamous cell lung carcinoma, pneumonectomy and adjuvant chemotherapy were performed. Brain recurrence and subsequent lung metastatic disease were uncontrolled by neurosurgery, holocranial radiotherapy and first-line chemotherapy. In August 2015, appearance of leptomeningeal carcinomatosis triggered severe clinical deterioration and threatened the patient's life. Anti-PD1 immune checkpoint inhibitor Nivolumab was initiated in an attempt to stop tumour growth, achieving a spectacular brain and pulmonary complete response and clinical improvement, without serious adverse effects. High expression PD-L1 level (100%) was found in the pathological tissue sample. Nivolumab was maintained for more than two years and stopped in December 2017 after 28 months of treatment, with no disease evidence. More than three years after its onset, the patient maintains an outstanding PS with complete tumour response and no evidence of disease in last surveillance CT scan and brain MRI.